IMPLEMENTASI PENGELOLAAN PAJAK REKLAME DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KOTA BONTANG - Lili Masmuji (Jurnal Paradigma (JP), 2017)
The purpose of this article is to describe and analyze the Advertising Tax Management Implementation in increasing local income as well as to determine its contribution to local revenue in Bontang city. The research finding concludes that the management of advertisement tax in Bontang is not running optimal. It is due to lack of achievement of targets. Within the last 5 years of the advertisement tax revenues did not always hit the target, so that its contribution to local revenue is relatively small. In fact, from advertisement tax promises to add other sources of income and a greater contribution has yet to be able to increase the revenue from advertisement tax. Advertisement tax revenue in Bontang caused by various factors:  Less effective in socializing the taxpayer regarding local regulation No. 02 Year 2011 regarding advertisement tax levies, and weak legal sanctions against the tax subject, so much the subject of taxes easily avoid taxation.